Hydrocarbon Columns of Oil and Gas Fields in the South Sumatra Basin - Veridaus Napitupulu; Miftahul Jannah; Michael Silaen; Herman Darman (Berita Sedimentologi, 2020)
The South Sumatra Basin is a prolific basin with a long history of oil and gas exploration that started in early 1900s. It is located in the southern part of Sumatra Island, Indonesia, where more than 300 oil and gas fields have been discovered. The basin contains multiple hydrocarbon reservoir horizons, from Pre-tertiary Basement to Miocene age. The kitchen areas also have various depths, with different levels of maturity. This petroleum system variation is reflected by the field size distribution and the heights of the hydrocarbon columns.Many authors have discussed the petroleum system of this basin and they are useful for providing regional geological perspectives. The oil and gas fields in South Sumatra are usually discussed independently by the operators. Different seismic vintages, density and quality make seismic correlations across the basin challenging. Apart from that, the data restriction is another hurdle in making correlation of the fields. Therefore, statistical studies of the fields and play level understanding become challenging.This study utilizes the Indonesian Petroleum Association Atlas of South Sumatra oil and gas fields, which was published in 1990. Several new fields, especially in fractured basement reservoirs, were added, based on recent publications. Additional information from the IHSE fields database was used to support the study. These data allow a statistical study on hydrocarbon column heights in the South Sumatra Basin. The result of this study could explain more about the charge and seal elements in the basin.